Interventional Radiology Management of Renal Pseudoaneurysms: Experience at a Tertiary Care Hospital - Gorsi, Ujjwal; Soundararajan, Raghuraman; Jugpal, Tejeshwar Singh; Lal, Anupam; Shetty, Sreedhara B; Kalra, Naveen; Kang, Mandeep; Sandhu, Manavjit Singh (Journal of Clinical Interventional Radiology ISVIR, 2020)
Objectives Renal pseudoaneurysms are multifactorial in origin, and angioembolization remains the mainstay of treatment. Few case reports have also described percutaneous embolization using glue or thrombin. Our study aimed to evaluate the predictors of active bleed by analyzing their etiology, morphology, imaging features, and treatment adopted. To the best of our knowledge, this is the largest such study done in India.Methods This was a retrospective study of patients treated for renal pseudoaneurysms between 2014 and 2019. We reviewed their clinical data, treatment modalities used, and clinical outcomes. We also assessed computed tomography angiography (CTA) and conventional angiography images.Results A total of 79 patients (54 males and 25 females) were included in the study. The mean age was 39.5 years (range 15–83 years). The most common cause was renal biopsy, followed by surgery. Of these, three patients (3.9%) had more than one lesion and 57% of pseudoaneurysms were seen in lower polar arteries. Active contrast extravasation was seen in 15.2% (n = 12) of the patients and 21.5% (n = 17) showed lobulations in CT and digital substraction angiography. The mean size of the pseudoaneurysms was 1.17 cm (SD 0.7); 22.8% of pseudoaneurysms were wide necked. The embolization was approached by endovascular (89.9%), percutaneous (10.1%), or both (1.3%) routes. Embolization was performed using microcoils (78.5%), gel foam (12.7%), N-butyl cyanoacrylate glue (8.9%), polyvinyl alcohol (8.9%), and thrombin (5.1%) either as a single agent or in combination. The technical success was achieved in all cases after the first procedure. Pseudoaneurysms with a wide neck (p = 0.03) and lobulations (p = 0.002) were associated with active contrast extravasation. Episodes of rebleeding were seen at a younger age (p-value = 0.02).Conclusion Minimally invasive methods remain the cornerstone in the management of renal pseudoaneurysms with high success rates. The morphology of pseudoaneurysms can help predict the risk of active bleeding and decide the type of intervention. Direct percutaneous injection into the aneurysm sac is an alternate technique and should be considered when an endovascular approach is challenging.
Keywords: renal pseudoaneurysm; angioembolization; coils; thrombin; cyanoacrylate glue